Study of Chromium Nitrate Coating Prepared by RF/DC Magnetron Sputtering - R., Hariharan; R. , Raja (International Journal of Psychosocial Rehabilitation, 2019)
The reasonable solution to the requirement of semi-solid forming tools and low-melting-point metals and alloys while using chromium nitrate coating (crN). This type of hard coating has excellent mechanical behaviour when working at high temperatures. We will develop the related hard coating based on stainless steel. This method is obtained by RF/DC microwave sputtering on HSS substrate (high-speed steel). The multilayers are characterized in terms of their hardness, wear, and corrosion resistance. The sputtering state on the crystal structure of the films is examined by X-ray diffraction (XRD), AFM (atomic force microscope), SEM (scanning electron microscope), and hardness by micropenetration. The chromium-metal interlayer through the film structure enhances the coating of the steel by reducing current, mobility, and the better coefficient of thermal expansion.